2021
DOI: 10.1021/acs.jpca.0c09999
|View full text |Cite
|
Sign up to set email alerts
|

Reactive, Inelastic, and Dissociation Processes in Collisions of Atomic Nitrogen with Molecular Oxygen

Abstract: Collisions of atomic nitrogen with molecular oxygen have been treated with the quasiclassical trajectory method (QCT) in order to obtain a complete database of vibrationally detailed cross sections and rate coefficients for reactive, inelastic, and dissociation processes. For reaction rate coefficients, the agreement with experimental and theoretical data in the literature is excellent on the whole available interval 300–5000 K, with reliable extension to 20,000 K. For the inelastic case and for dissociation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
39
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 72 publications
8
39
0
Order By: Relevance
“…Presently, there is an acceptable consensus among the experimental data available in the literature on the R1 reaction thermal rate constant. , Specifically, the rate constant approximation proposed by Fernandez et al, elaborated initially for the temperature interval T = 400–1220 K [ k ( T ) = 1.20 × 10 6 T 2.15 exp­(−2557/ T ) cm 3 mol –1 s –1 ], in fact, , is in good consistency with the other measurements in a much wider temperature range. ,, However, there are still problems with the quantitative interpretation of these data. Particularly, some theoretical studies , ,, using the precise potential energy surfaces (PESs) and advanced methods for calculating the thermal rate constants, such as the quasi-classical trajectory (QCT) approach and even wave packet (WP) dynamics, markedly (by more than an order of magnitude) underestimated the low-temperature measurements. , Only just recently, Esposito and Armenise have succeeded in QCT simulations in obtaining the R1 thermal rate constant, which is consistent with experimental data over a wide temperature range.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Presently, there is an acceptable consensus among the experimental data available in the literature on the R1 reaction thermal rate constant. , Specifically, the rate constant approximation proposed by Fernandez et al, elaborated initially for the temperature interval T = 400–1220 K [ k ( T ) = 1.20 × 10 6 T 2.15 exp­(−2557/ T ) cm 3 mol –1 s –1 ], in fact, , is in good consistency with the other measurements in a much wider temperature range. ,, However, there are still problems with the quantitative interpretation of these data. Particularly, some theoretical studies , ,, using the precise potential energy surfaces (PESs) and advanced methods for calculating the thermal rate constants, such as the quasi-classical trajectory (QCT) approach and even wave packet (WP) dynamics, markedly (by more than an order of magnitude) underestimated the low-temperature measurements. , Only just recently, Esposito and Armenise have succeeded in QCT simulations in obtaining the R1 thermal rate constant, which is consistent with experimental data over a wide temperature range.…”
Section: Introductionmentioning
confidence: 78%
“…The reaction of the ground-state atomic nitrogen ( 4 S) with normal oxygen molecules is one of two principal elementary channels involved in the Zeldovich mechanism for high-temperature conversion of air N 2 to nitrogen oxides (NO x ), while this mechanism, also known as the “thermal NO” one, underlies the complex chemical kinetic models describing the NO x pollutant emission from combustion or high-temperature industrial processes and the nitrogen oxidation in re-entry flows. The kinetics of the R1 process has been extensively studied for a long time, both experimentally (see for the low-, elevated-, , and high-temperature measurements , ) and theoretically. , In addition, there are some available experimental and theoretical data ,,,,,,,, on the nascent distribution of vibrationally excited NO­( v ) formed in the R1 reaction.…”
Section: Introductionmentioning
confidence: 99%
“…135 perimental data [136][137][138] are extracted from the vibrational relaxation time parameters (pτ vib ) following the Bethe-Teller model. 139 In a recent study, 134 QCT calculated VR rates are found to significantly underestimate the experimental results. The VR rates calculated from QCT simulations in this work using the HB and GB schemes are shown in Figure 5.…”
Section: Statementioning
confidence: 92%
“…The reverse reaction and the N 2 dissociation are also studied recently and rate expressions are reported. 133,134 In another recent study the PESs for the two lowest triplet states of N 2 O have been reconsidered based on MRCI+Q/aug-cc-pVTZ calculations. 135 The grid was considerably extended, in particular for the diatomic separation (r), and in the long range interaction region (along R) was treated more accurately.…”
Section: Statementioning
confidence: 99%
See 1 more Smart Citation